Organizational change: Considering truth and buy-in - Jason A. Hubbart (Administrative Sciences, 2023)
Organizational change initiatives are often undertaken to update major business structural components or practices to meet the evolving needs of a changing industry. Unfortunately, explicit emphasis on the importance of truth and buy-in is missing from most, if not all, change initiatives. Including these factors is essential because the acceptance of explanations (truth) for change, resulting in stakeholder buy-in and commitment to change, may be among the most significant challenges to organizational change success. Indeed, the absence of leadership-conveyed truth-telling, and stakeholder truth acceptance, restrains the ability to grow, change, develop and evolve as an organization. Thus, insufficient truth acceptance and buy-in results in deficient stakeholder engagement and a decreased likelihood of organizational change initiative success. Moreover, the benefits of truth acceptance and buy-in stretch well beyond organizational change initiatives and positively influence work performance, commitment, satisfaction, and turnover. Therefore, the concepts of truth and buy-in are multi- and inter-organizational and essential at all levels of an organization. The purpose of this communication is to consider the general role(s) of truth and buy-in in the organizational change process and to serve as a reminder of the importance of explicitly including and achieving both early in the change initiative process.
Keywords: 350; buy-in; change initiative; engagement; leadership; management; organizational change; trust; truth